Digital technology enablement and policy synergy: Strategic evolution of digital transformation for climate governance in China (2015-2024) - Chang, Yang (COMMICAST, 2025)
Climate change governance has become a systemic global challenge involving justice, security, and sustainable development, with digital technologies increasingly reshaping governance strategies. Against this backdrop, China, as the world’s largest developing country and carbon emitter, has actively embedded digital technologies into its climate policy framework since the Paris Agreement (2015). Drawing on 48 core policy documents issued by the State Council and related ministries, the research employs textual and discourse analysis combined with word frequency extraction, semantic clustering, and thematic module analysis. The findings reveal six interlinked thematic domains, policy framework and institutional design, energy transition, sectoral and regional governance, ecological conservation, market mechanisms, and capacity-building, through which digital technology functions not only as a technical instrument but also as a discursive and institutional driver. The study identifies a dynamic evolution of policy tool portfolios, shaped by path dependency, pilot-driven mechanisms, and institutional synergy between administrative authority and digital intermediaries. This research contributes both theoretically and practically by developing a “technology discourse tool” framework that explains how digital technologies are discursively embedded and translated into institutional practices. Empirically, it shows that China’s governance model has generated replicable digital governance templates, offering strategic lessons for other developing countries seeking to integrate digitalization with climate governance. The study concludes that digital technologies, when embedded in policy discourse and institutional tools, can significantly enhance governance efficiency, accountability, and international discourse power in climate policymaking.